Being Smart About Gluten and Gluten-Free Issues, Part 1: What Are the Health Concerns Surrounding Gluten? - Abigail Dicks; Amy Harder; Amy Simonne (EDIS)
Are you an inquisitive consumer who asks what the big deal is about gluten free? Ask no more; this article is the first in a three–part series about gluten. This 7-page fact sheet identifies health conditions surrounding the ingestion of gluten. The resources used in this article are research and evidence based and/or peer reviewed to provide straightforward and simple information about a few gluten-related topics. Written by Abigail Dicks, Amy Harder, and Amy Simonne, and published by the UF Department of Agricultural Education and Communication, January 2013.